Aktivitas Antiinflamasi Crude Extract Fukoidan dari Sargassum crassifolium pada Sel RAW 264.7 yang Diinduksi LPS - Hikariastri, Pangartika; Winarno, Hendig; Kusmardi, Kusmardi; Laksmitawati, Dian Ratih; Abdillah, Syamsudin (Jurnal Kefarmasian Indonesia, 2019)
Inflammation is known as the basic mechanism underlying various chronic diseases. Macrophage activation by inflammatory stimulus induces the release of inflammatory mediators, thus the mediators becoming a promising target of anti-inflammatory drug development. Previous studies indicated that fucoidan has anti-inflammatory activity by inhibiting the release of proinflammatory mediators. The aim of this study is determining anti-inflammatory activity of fucoidan crude extract form Sargassum crassifolium Garut waters by observing its effect on proinflammatory cytokines TNF-α, IL-1β, dan IL-6. Fucoidan is a polysaccharide substance which has various characteristics, depending on the source and the extraction method which is influencing its bioactivity. Sargassum crassifolium collected from Garut-West Java is extracted using diluted HCl 0,1 M and precipitated with ethanol to obtain fucoidan crude extract. The crude extract is tested on LPS-induced RAW 264.7 cells to evaluate its effect on TNF-α, IL-1β, and IL-6 level using ELISA method. The result showed that fucoidan crude extract decreased the level of TNF-α by the dose of 25 and 50 μg/ml, and decreased the level of IL-1β and IL-6 by the dose of 25 μg/ml. The dose of 50 μg/ml failed to inhibit IL-1β and IL-6 production. This study showed that fucoidan crude extract derived from S. crassifolium has anti-inflammatory activity to RAW 264.7 cells by the dose of 25 μg/ml.